A review on graph representation for object-oriented programming - Farooq Khattak, Umar; Ali Hussein Al Naffakh, Hussein; Alı, Aıtızaz (BIO web of conferences, 2024)
Relationships and connections between entities are typically represented by graphs, a fundamental data structure in computer science. A graph illustrates the control flow among statements within a program, whereas a dependence graph delineates the interrelationships among various objects within it. The object-oriented paradigm introduces numerous innovative concepts, including encapsulation, inheritance, polymorphism, and dynamic binding. A complete object-oriented graph representation entails structuring and conceptualizing a graph based on the principles of object-oriented programming (OOP). Several models have been suggested previously designed to depict the diverse features of object-oriented programming. This study distinguishes between partial and fully object-oriented graph representations. It also analyses the fully object-oriented graph representation models.